النمذجة الرياضية للإدارة بالاحتكاك في آلات التشغيل ذات الضبط العالي الدقة - زهرة محمد (Latakia University Journal -Engineering Sciences Series, 2019)
إن الإدارة ( نقل الحركة ) بالاحتكاك ذات الاسطوانة - القضيب هي مثال عن المحرّك المستقيم عالي الدقة. كما أن الإدارة بالاحتكاك ذات الاسطوانة - القضيب تقدّم ميزات تحكم ذات حركة رجوعية ضعيفة, ونطاق عدم رجوع, وذلك نتيجة للتعديل المرن داخل منطقة التماس بحسب نظرية هرتز. إضافة إلى أنها تعطي البساطة في التصميم الأولي، والتصميم القابل للتوسع أو التمدد إلى مجالات أطول( بعلو ترتيب الأمتار ), إذ تبدي مجهوداً بتكلفة هامشية فقط في التصميم والتطبيق. إلا إن الإدارة بالاحتكاك ذات الاسطوانة - القضيب لم تُستخدم على نطاق واسع، ومن المحتمل أن يكون السبب في ذلك هو عدم التأكد بخصوص أمور محددة مثل: القدرة على الإدارة، والكسب في نقل الحركة, والتبولوجيا ( دراسة الخصائص الهندسية التي لا تتأثر بتغير الحجم أو الشكل ), ونظافة قضيب الإدارة - سطح التماس. إن مواجهة عدم التأكد هذا, والمتعلق بخصوص أمور محددة في القدرة على الإدارة بالاحتكاك، تمت بإجراء تحليل بقصد تأمين أدوات تصميم لجيل جديد من آلات التشغيل. وتطوير نموذج رياضي ليتقصى سلوك سطحي التماس باستخدام نظرية هرتز لإجهادات التماس. وهذا ما سنقدمه في هذا البحث, بالإضافة لأهداف أخرى للدراسة تضمنت منهجيات من اجل تحديد الصلابة الستاتيكية والديناميكية بوصفها تابعاً للحمل, وإدخال الحركة (الديناميكا) بوصفها تمثيلاً للإدارة - تردد القوة. وتم أيضا وصف للنموذج, وإجراء مقارنات مع النتائج التجريبية. The friction Drive (transmission) with the roller-the bar is an example of a high-precision rectilinear actuator. And also friction Drive with the roller-the bar offers control advantages with a retrograde movement is weak, and the scope will not return, as a result of the elastic amendment within the contact area according to the theory of Hertz. Add to that, it gives the simplicity in the initial design and design viable for expansion or expansion to areas longer (order of meters height), so show only a marginal cost of effort in design and application. However, the friction Drive with the roller—the bar not used widely, and is likely to be the reason for this is uncertainty regarding the specific matters such as: the ability to drive-force, and gain in the transmission, and topology (the study of geometric properties which are not affected by change size or shape), and the cleanliness of drive bar-interface. To face of this uncertainty, that is related to specific matters concerning the ability to drive-force, an analysis has the aim of ensuring design tools for a new generation of machine tool, and the development of a mathematical model to explore the behavior of surface contact using the theory of Hertz contact stresses. This is what we will present in this research, in addition to other objectives of the study included the methodologies in order to determine Static and dynamic stiffness as a function of load, and input dynamics as represented by drive-force frequency. It was also a description of the model, and comparisons with experimental results.